Optimalisasi Pengelolaan Berkas Rekam Medis Pasien pada Puskesmas Dasan Agung - Maspaeni Maspaeni; Lalu Moh. Nurkholis; Baiq Rika Diana (Explore, 2022)
Dasan Agung Public Health Center is one of the health service agencies in the city of Mataram. The Dasan Agung Health Center has 5 polyclinics, namely General Poly, Dental Poly, Children's Poly, and Maternal and Child Health Poly. Currently, the data processing of patient medical record files at the Dasan Agung Public Health Center is still done manually. This condition makes the patient's medical record file management system not practical and efficient, because the patient's medical record file is still possible to be tucked or scattered. To overcome the problems faced, the Dasan Agung Public Health Center needs an effective and efficient information system to optimize the management of patient medical record files at the Dasang Agung Public Health Center.